2020
DOI: 10.1038/s41598-020-76402-w
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of zinc oxide nanoparticles by cell-biomass and supernatant of Lactobacillus plantarum TA4 and its antibacterial and biocompatibility properties

Abstract: This study aims to utilize the cell-biomass (CB) and supernatant (CFS) of zinc-tolerant Lactobacillus plantarum TA4 as a prospective nanofactory to synthesize ZnO NPs. The surface plasmon resonance for the biosynthesized ZnO NPs-CFS and ZnO NPs-CB was 349 nm and 351 nm, respectively, thereby confirming the formation of ZnO NPs. The FTIR analysis revealed the presence of proteins, carboxyl, and hydroxyl groups on the surfaces of both the biosynthesized ZnO NPs that act as reducing and stabilizing agents. The DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 63 publications
(104 reference statements)
1
39
0
Order By: Relevance
“…Agar well diffusion method was used to investigate the antibacterial activity of biosynthesized ZnO NPs against poultry-associated foodborne pathogens following the procedure outlined in our previous study [26]. Briefly, the bacterial strains were grown until they reached the 0.5 McFarland turbidity standards and a lawn of bacterial strain was made by spreading them uniformly onto a nutrient agar (NA) (Merck, Darmstadt, Germany) plate using a sterile cotton swab.…”
Section: In Vitro Antibacterial Activity Of Biosynthesized Zinc Oxide Nanoparticles 241 Agar Well Diffusion Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Agar well diffusion method was used to investigate the antibacterial activity of biosynthesized ZnO NPs against poultry-associated foodborne pathogens following the procedure outlined in our previous study [26]. Briefly, the bacterial strains were grown until they reached the 0.5 McFarland turbidity standards and a lawn of bacterial strain was made by spreading them uniformly onto a nutrient agar (NA) (Merck, Darmstadt, Germany) plate using a sterile cotton swab.…”
Section: In Vitro Antibacterial Activity Of Biosynthesized Zinc Oxide Nanoparticles 241 Agar Well Diffusion Methodsmentioning
confidence: 99%
“…The established procedure from our previous study [26] was followed for the biosynthesis of ZnO NPs with some modifications. Briefly, 20 mL of supernatant from zinc-tolerant L. plantarum TA4 was mixed with 80 mL of 500 mM aqueous zinc nitrate (Zn(NO 3 ) 2 •6H 2 O) solution.…”
Section: Zinc Oxide Nanoparticles Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial activity of biosynthesized ZnONPs was studied against Gram-positive ( S. epidermidis and S. aureus ) and Gram-negative ( Salmonella sp. and E. coli ), and it was observed that ZnONPs were more effective against Gram-positive bacteria [ 123 ]. Another amnestic work reports the biofabrication of ZnO, MnO 2 and MgONPs by deploying a rhizophytic bacteria Paenibacillus polymyxa strain Sx3 [ 124 ].…”
Section: Strategies For Synthesis Of Nanoparticles Using Microbesmentioning
confidence: 99%
“…Namely, evidence-supported, accessible resources which they can use to support workers with concussion in their recovery and return-to-work. Inappropriate communication which is limited to a brief exchange within a doctor's office, an emergency department, or a phone call with a workers' compensation board case manager, may result in poor understanding and difficulty to recall the discharge care or return-to-work plan (39).…”
Section: Comparison With Previous Workmentioning
confidence: 99%